Development of Scale to Measure Agripreneurs Attitude towards Entrepreneurial Climate (Indian Journal of Extension Education, 2022)
Attitude plays a crucial role in influencing one’s behaviour with respect to a particular psychological object. To measure the attitude of farmers towards entrepreneurial climate for agrienterprise development, need was realized to devise a scale and a Likert’s Summated Rating scale was constructed by following the standard methodology suggested. Attitude towards entrepreneurial climate was categorized in six specific dimensions viz. Institutional factors, psychological factors, cognitive factors, managerial factors, sociological factors and economic factors. A total of 141 items were constructed and was sent to 124 experts through email, Google docs form and handed over personally by visiting to the experts. Based on the 43 experts’ responses 72 items were screened out for item analysis. The scale was administered to 80 agripreneurs of Uttar Pradesh. The odd-even method was followed for testing reliability of the scale and reliability co-efficient was 0.66. The validity of the scale was examined with the help of face and content validity. The scale developed finally consisted of 44 items (36 positive and 8 negative).